07-06-2012, 05:47 PM

Here is the proof for Weight of Elephant is Equal to Weight of ant!!!

Let the weight of an Elephant be ‘X’

Let the weight of an Ant be ‘Y’

Let the total weight be ‘2V’

Therefore

X+Y=2V--------------- eqn 1

X=2V-Y---------------- eqn 2

Y=2V-X---------------- eqn 3

Multiply equation 3 by (-1)

-Y= -2V+X------------ eqn 4

Multiply equation 4 by ‘X’

-Y(X) = -2VX+X2

Put the value of ‘X’ in LHS

-Y (2V-Y) = -2VX + X2

-2VY + Y2 = -2VX + X2

Adding V2 on both sides

X2 – 2VX + V2 = Y2 – 2VY + V2

(X – V)2 = (Y – V)2

Taking Square root on both sides

(X-V) = (Y-V)

X=Y-V+V

X = Y

Weight of an elephant = Weight of an ant.

Hence proved.:-p

Share your Study Materials with us : Click Here